ANALISIS PENERAPAN PRINSIP-PRINSIP PENGELOLAAN BUMDES WIRAKARYA DESA TANJUNG SIMANDOLAK KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI TAHUN 2019 - Seli Okta Kumala; Auradian Marta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The establishment of the Bumdes Wirakarya begins with a Village Deliberation by establishing the Bumdes Management Team, Monitoring Team and Verification Team and Evaluation of Bumdes Activities with Initial Capital from the Village Fund Budget or APBDes, which is Rp. 310,000,000 of the ADD funds disbursed in two stages, namely 2018 and 2019 so that the use or utilization of funds that have been carried out is in accordance with applicable procedures and laws, but the application of the principles of managing BUMDes Wirakarya in Tanjung Simandolak Village, Benai District, Kuantan Regency Singingi is not working properly. The objectives of this research are: To find out the management principles of BUMDes Wirakarya which are cooperative, participatory, emancipatory, transparent, accountable and sustainable in Tanjung Simandolak Village, Benai District, Kuantan Singingi Regency and in addition to knowing the factors supporting and inhibiting the principles of BUMDes management. masterpiece. Furthermore, the data collection techniques used were interviews and documentation. While the source of data used is primary data obtained from the research location in the form of research informants and supported by secondary data, namely documents related to interviews, observations, and document studies. The location of this research is in BUMDes Wirakarya Tanjung Simandolak Village. The results and discussion of this study indicate that the application of the principles of managing the Wirakarya Village-Owned Enterprises which are cooperative, participatory, emancipatory, transparent, accountable and sustainable, does not appear to be optimal in the form of poor cooperation between BUMDes managers and village governments and communities, where all the management has not been able to participate maximally as well as the community members, the lack of information and socialization of most residents of Tanjung Simandolak Village are less able to maintain and care for the existence of BUMDes such as the zoom futsal field which produces nothing and is just wasted. The supporting and inhibiting factors for the management principle of BUMDes Wirakarya in Tanjung Simandolak Village, Benai District, Kuantan Singingi Regency where the supporting factors in terms of government commitment in poverty alleviation and village empowerment through BUMDes are very high. This is evidenced by the injection of BUMDes funds from village funds, district budgets, provincial budgets and related ministries. While the inhibiting factor is that the village's budget in running the BUMDes business exists, but it is still very small to develop a large business, then human resources and community participation are still lacking in the management of BUMDes. Keywords: cooperative, participatory, emancipatory, transparency, accountable and sustainable